Motivating and engaging others: driving practice change. (2nd March 2019) - Kerrigan, Lynne
Abstract : Do changes introduced within your practice go no further; are they met with negativism, disinterest or even resistance? Are new ideas dismissed by a culture of complacency and inertia? Change can be a difficult and even uncomfortable process to go through and when poorly handled can lead to high levels of stress amongst the team. The ability to change is crucial, however, to the success of any organisation and has never been more important than it is in today's evolving healthcare environment. To manage change effectively requires time and dedication. This article aims to introduce novice/aspiring leaders to elements of change theory and make practical suggestions as to how to plan and implement a change in practice.